Multiple photodetachment of atomic anions via single and double core-hole creation. (24th August 2020) - Schippers, S; Perry-Sassmannshausen, A; Buhr, T; Martins, M; Fritzsche, S; Müller, A
Abstract: We review the recent experimental and theoretical progress in K -shell detachment studies of atomic anions. On the experimental side, this field has largely benefitted from technical advances at 3rd generation synchrotron radiation sources. For multiple detachment of C −, O −, and F − ions, recent results were obtained at the photon-ion merged-beams setup PIPE which is a permanent end station at beamline P04 of the PETRA III synchrotron light source in Hamburg, Germany. In addition to a much increased photon flux as compared to what was available previously, the PIPE setup has an extraordinary detection sensitivity for heavy charged reaction products that allows one to study detachment processes with extremely low cross sections in the kilobarn range, e.g., for processes involving the simultaneous creation of two core-holes by a single photon as observed in the net triple detachment of F − and the net five-fold detachment of C − . Moreover, hitherto disregarded photodetachment resonances have been discovered, which exhibit a variety of line shapes. For O − the core-hole lifetime could be determined precisely from a high-resolution measurement of a photodetachment resonance. These experimental findings pose new challenges for state-of-the-art atomic theory and require calculations combining photoexcitation (ionization) with decay cascade processes that follow after initial core-hole production.